Alternativas para la protección y conservación de las fuentes hídricas pertenecientes a la microcuenca de la Quebrada Balsas - Ramos Cueva, María Fernanda (2015)
The current project identifies the causes of the alteration in the quality of water bodies belonging to the watershed subject of study. Firstly, it has been determined that hog and cattle farming are the main activities that affect water resources. Such information was obtained through interviews and field technical visits to producers in rural areas. In addition, this paper presents some basic concepts related to watershed protection and the environmental benefits related. The objective is focused on designing an integrated preservation proposal based on a reforestation plan and physical protection in a reference area of 50,000 m2 from the catchment areas of water, and the implementation of the deep litter method as an alternative to substitute the current system of hog farming, taking as an example a farm with 25 fattening pigs and 5 pigs for breeding. To conclude, the research determines the assessment of impacts of both the traditional system of production and deep litter system and its feasibility. At the end, there will be an analysis of the social dimension concerning the number of beneficiaries, the economic and technical feasibility in relation to the product used and the species selected for reforestation, resulting in a positive direction in the implementation of the project.